PERCEIVED EFFECTIVENESS AND CONSTRAINTS IN INNOVATIVE EXTENSION METHODOLOGY â€œMASTER TRAINERS TRAINING PROGRAMMEâ€ IN PRAKASAM DISTRICT OF ANDHRA PRADESH - SARADA, O. (The Journal of Research, PJTSAU, 2019)
Training can be regarded as an age long concept which performs the therapeutic function of shaping knowledge, skill and attitude that are required for effective performance of duties and or assignment (Adisa and Okunade, 2005).. Using master trainers is a cost-effective way to introduce new technologies to the farmers. It is increasingly acknowledged that public extension services in developing countries are no longer able to meet the changing needs of farmers. As a result, the sector has, over the last decade, been going through a transformative process from the linear model of technology transfer to the more pluralistic demanddriven extension. These approaches focus on farmers as the principle agents of change in their communities and, therefore, enhance their learning and empowerment, thereby increasing their capacity to adapt/innovate and train other farmers. One such approach is the Master trainer approach to disseminate information/knowledge to the farmers.